PENANAMAN KARAKTER PERCAYA DIRI MELALUI LATIHAN DAN PEMENTASAN TARI PADA PESERTA KELAS REMAJA DI MAHALAWU DANCE STUDIO KABUPATEN MAGETAN - Rahayu, Zaidatul Chusnul; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2025)
Self-confidence is one aspect of personality that is important and helps humans in their personal development, especially for adolescents. In the current era, most teenagers have feelings of insecurity in showing their abilities. This feeling of insecurity is part of the lack of self-confidence that needs to be overcome. Mahalawu Dance Studio as an education in the non-formal sphere in addition to producing professional dancers also forms character, one of which is self-confidence. The formulation of the problem looks at how the cultivation of self-confidence character through dance training and performance on adolescent class participants at Mahalawu Dance Studio Magetan Regency. The research approach uses descriptive qualitative methods with a case study design. Data collection techniques using in-depth interviews, moderate participant observation and documentation. Data analysis techniques through analysis of the Miles and Huberman model consisting of data collection, data reduction, data presentation and conclusion drawing. The results showed the process of cultivating self-confidence character by Mahalawu Dance Studio through reinforcement. The gradual process contains four stages, namely: (1) Establishing a commitment to recognizing participants' character and initial learning foundation (2) Conditioning the participants' behavior through recognition and reinforcement. (3) Building awareness of participants' behavior through repetition of reinforcement. (4) Creating the impact of behavior habituation on themselves and the studio. The process involving reinforcement consists of seven rewards and six punishments in verbal and non-verbal forms. The final findings show that the process of character cultivation in non-formal education requires the establishment of commitment at the beginning to strengthen the foundation of self-concept and the relationship between the giver and receiver of stimulus.